Sulfonated resin for heavy metal adsorption and preparation method thereof
By polymerizing and sulfonating treatment on the silicon carbide nanowire framework, a sulfonated resin with high adsorption capacity and stability was prepared, which solved the problem of poor adsorption effect of existing resins on heavy metals.
Patent Information
- Application Number
- CN202510094270.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing adsorption resin has limited complexing effect on heavy metals, and has low adsorption removal rate, which cannot meet environmental protection requirements.
A sulfonated resin with a large adsorption capacity and active groups was prepared by using silicon carbide nanowires as the framework.
It improves the adsorption capacity and removal effect of heavy metal ions, enhances the strength and stability of the resin, and is suitable for reuse.
Smart Images

Figure BDA0005252424930000071 
Figure BDA0005252424930000072 
Figure BDA0005252424930000081
Abstract
Description
Technical Field
[0001] The present application relates to an adsorption resin, and more specifically, to a sulfonated resin for heavy metal adsorption and a preparation method thereof. Background Art
[0002] Heavy metal wastewater mainly comes from wastewater discharged by mining, smelting, electrolysis, electroplating, pesticides, medicines, paints, pigments and other enterprises. If heavy metal wastewater is not treated, it will seriously pollute the environment. Therefore, for the wastewater treatment of these industries, the method of using heavy metal removal resin can efficiently remove heavy metal ions in wastewater and achieve environmental governance and protection. However, the current adsorption resin has limited complexing effect on heavy metals, and the adsorption removal rate of heavy metals is low, which cannot meet environmental protection requirements well. Therefore, how to provide an adsorption resin with a large capacity so that it can better achieve the adsorption of heavy metals is a problem that needs to be solved at present. Summary of the invention
[0003] In order to solve the problems of low adsorption capacity of adsorption resin and limited complexing effect on heavy metals, the present application provides a sulfonated resin for heavy metal adsorption and a preparation method thereof.
[0004] In a first aspect, the present application provides a method for preparing a sulfonated resin for heavy metal adsorption, comprising the following steps: S1: uniformly mixing styrene, divinylbenzene, methyl acrylate, toluene, isobutyl alcohol, normal alkanes, liquid wax, gasoline, BPO, AIBN, liquid bromine, and nitrobenzene to obtain a monomer formulation; mixing water, cellulose, calcium carbonate, boric acid, calcium chloride, and sodium chloride to obtain an aqueous phase mixture; uniformly mixing the monomer formulation and the aqueous phase mixture, heating, and keeping the mixture warm to obtain a polymer; S2: washing the polymer with water, washing with an organic solvent, drying the powder and sieving it to obtain an intermediate product; S3: Mix concentrated sulfuric acid and mother acid to obtain reaction acid, mix reaction acid, ethylene dichloride and intermediate product evenly, heat up, keep warm for reaction, and cool down to obtain sulfonated material; S4: Dilute and wash the sulfonated material with sulfuric acid solution, wash with water, then add chloroacetic acid, phosphorous acid and liquid alkali for transformation and stabilization, drain the liquid, wash with water, filter and dry to obtain sulfonated resin.
[0005] By adopting the above scheme, the preparation method is relatively simple, the polymerization is relatively complete, styrene, divinylbenzene, and methyl acrylate are copolymerized with aromatic hydrocarbon grafted silicon carbide nanowires as the skeleton, the polymerization process is evenly dispersed, and the obtained adsorption resin has a large average pore size, a large specific surface area, and a large adsorption capacity. The intermediate product is further sulfonated to introduce more active sulfonic acid groups, and the copolymer side chain is oxidized to carboxyl and hydroxyl groups, which jointly replace, complex and adsorb heavy metal ions, and have a good removal effect on heavy metal ions. Silicon carbide nanowires have high strength and toughness, and are resistant to chemical corrosion, which improves the strength of the obtained resin. The obtained resin is not easy to break after repeated use, and the dissolution loss is small, which ensures the stability of adsorption. By grafting aromatic hydrocarbons on silicon carbide nanowires, steric hindrance is increased to make the obtained resin structure more stable.
[0006] In a specific implementation scheme, the mass parts of each component in the monomer formulation in S1 are as follows: 190-220 parts of styrene, 180-200 parts of divinylbenzene, 15-40 parts of methyl acrylate, 25-45 parts of aromatic grafted silicon carbide nanowires, 45-70 parts of toluene, 50-100 parts of isobutanol, 50-100 parts of normal alkanes, 100-200 parts of liquid wax, 100-200 parts of gasoline, 2-5 parts of BPO, 3-5 parts of AIBN, 5-10 parts of liquid bromine, and 5-10 parts of nitrobenzene; the mass parts of each component in the aqueous phase mixture are as follows: 2000-2200 parts of water, 5-10 parts of cellulose, 5-10 parts of calcium lignin sulfonate, 5-10 parts of boric acid, 50-70 parts of calcium chloride, 50-80 parts of sodium chloride, 2-10 parts of methylene blue, and 5-10 parts of gelatin.
[0007] By adopting the above scheme, a certain mass of aromatic hydrocarbon grafted silicon carbide nanowires is added to the monomer configuration material, and the toluene content is increased, so that the polymer grown on the silicon carbide skeleton generates more micropores without reducing the strength, thereby improving the adsorption capacity. This is suitable for the preparation steps of the present application, has a high yield, few impurities, an appropriate degree of cross-linking, and the obtained adsorption resin has a uniform structure and a large capacity.
[0008] In a specific embodiment, the mass ratio of styrene, divinylbenzene, aromatic hydrocarbon grafted silicon carbide nanowires, and toluene is (5.5-6.5): (5-6): 1: 1.5.
[0009] By adopting the above scheme, the strength and adsorption performance of the obtained resin are better. The polymer is based on the aromatic hydrocarbon grafted silicon carbide nanowires and is full of micropores. The resin obtained by polymerization has a uniform structure, a large specific surface area and a high porosity.
[0010] In a specific embodiment, the preparation steps of aromatic grafted silicon carbide nanowires include: adding tetrakis(4-carboxyphenyl)silane and silicon carbide nanowires to an ethanol aqueous solution, stirring evenly, adjusting the pH value, heating for reaction, centrifuging, washing, and drying to obtain aromatic grafted silicon carbide nanowires.
[0011] By adopting the above scheme, the preparation method is simple. At the same time, it may be because tetra(4-carboxyphenyl)silane has a large steric hindrance, which improves the fixation effect of silicon carbide nanowires and polymers, makes the structure more stable, increases the amount of toluene and the number of micropores, and increases the carboxyl content. The carboxyl groups are evenly distributed on the silicon carbide nanowires, further improving the adsorption capacity inside the adsorption resin.
[0012] In a specific embodiment, the silicon carbide nanowires have a diameter of 0.1-1.0 μm and a length of 10-100 μm.
[0013] Under the above-mentioned size, the carbon nanowires are relatively thin and have a higher aspect ratio. They can be evenly distributed in the system while forming a certain degree of interlacing and entanglement, providing a better polymer skeleton effect, and the obtained adsorption resin has a larger capacity.
[0014] In a specific implementation scheme, the acid concentration in S3 is 90-94vt%, the mixing time is 25-35 minutes, the heating temperature is 80-115°C, the insulation time is 8-8.5 hours, and the cooling temperature is 40-50°C.
[0015] By adopting the above scheme, the sulfonation effect is good, the obtained resin has more active groups, and at the same time will not significantly damage the strength of the silicon carbide nanowire skeleton, so the obtained adsorption resin has better performance.
[0016] In a specific embodiment, the dilution washing step in S4 includes: washing with 70vt%, 45vt%, and 20vt% dilute sulfuric acid solutions in sequence, and the transition stabilization time is 30-40 minutes.
[0017] By adopting the above scheme, washing is performed in sequence with acid solutions of different concentrations, and the washing is more thorough, the micropores of the obtained resin are more uniform, and the resin has a larger capacity.
[0018] In a second aspect, the present application provides a sulfonated resin for heavy metal adsorption, which is prepared using the above steps.
[0019] The adsorption resin prepared by the above steps is polymerized with silicon carbide nanowires as the skeleton, has an appropriate degree of crosslinking, a stable skeleton, a large number of micropores, a large number of sites such as active carboxyl groups and hydroxyl groups that can replace heavy metal ions, a large adsorption capacity, and a good adsorption effect on heavy metals.
[0020] In summary, this application has the following beneficial effects: The present application adopts co-polymerization of multiple monomers, uses silicon carbide nanowires as a skeleton for polymerization, prepares an adsorption resin and sulfonates it, and limits the process parameters of each step. The prepared adsorption resin has an appropriate degree of cross-linking, a stable mechanical skeleton during the swelling process, and is fully sulfonated. The prepared adsorption resin has more active groups to replace heavy metal ions and has a large number of micropores, and is suitable for the adsorption of heavy metals. DETAILED DESCRIPTION
[0021] To further help understand the technical solution of the present invention, several specific embodiments are provided to describe the technical solution of the present invention in more detail. All the embodiments described are only partial embodiments of the present invention, not all of them; the embodiments can be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments. The following embodiments are further explanations of the present invention, and the present invention is not limited thereto.
[0022] Tetrakis (4-carboxyphenyl) silane was purchased from Nanchang Conge Pharmaceutical Technology Co., Ltd.; silicon carbide nanowires including those with a diameter of 0.1-0.5 μm and a length of 10-50 μm, those with a diameter of 1-5 μm and a length of 50-100 μm, and those with a diameter of 0.1-0.5 μm and a length of 100-150 μm were purchased from Shanghai Naio Nano Technology Co., Ltd.; the remaining experimental reagents, unless otherwise specified, were conventional commercial brands or obtained through conventional preparation processes.
[0023] Preparation example: Preparation Example 1: Add 5 g of tetrakis(4-carboxyphenyl)silane and 5 g of silicon carbide nanowires to 60 vt% ethanol aqueous solution, stir evenly, adjust the pH value to 6, heat to 75° C. and stir for 2 hours, centrifuge, wash twice with deionized water, and dry to obtain aromatic grafted silicon carbide nanowires.
[0024] The silicon carbide nanowires in this preparation example have a diameter of 0.1-0.5 μm and a length of 10-50 μm.
[0025] Preparation Example 2: Add 5 g of r-aminopropyltriethoxysilane and 5 g of silicon carbide nanowires to 60 vt% ethanol aqueous solution, stir evenly, adjust the pH value to 6, heat to 75°C and stir for 2 hours, centrifuge, wash twice with deionized water, and dry to obtain aminosilane-grafted silicon carbide nanowires.
[0026] The silicon carbide nanowires in this preparation example have a diameter of 0.1-0.5 μm and a length of 10-50 μm.
[0027] Preparation Example 3: Add 5 g of tetrakis(4-carboxyphenyl)silane and 5 g of silicon carbide nanowires to 60 vt% ethanol aqueous solution, stir evenly, adjust the pH value to 6, heat to 75° C. and stir for 2 hours, centrifuge, wash twice with deionized water, and dry to obtain aromatic grafted silicon carbide nanowires.
[0028] The silicon carbide nanowires in this preparation example have a diameter of 1-5 μm and a length of 50-100 μm.
[0029] Preparation Example 4: Add 5 g of tetrakis(4-carboxyphenyl)silane and 5 g of silicon carbide nanowires to 60 vt% ethanol aqueous solution, stir evenly, adjust the pH value to 6, heat to 75° C. and stir for 2 hours, centrifuge, wash twice with deionized water, and dry to obtain aromatic grafted silicon carbide nanowires.
[0030] The silicon carbide nanowires in this preparation example have a diameter of 0.1-0.5 μm and a length of 100-150 μm. Example
[0031] Example 1 This embodiment includes the following components by mass: 190g styrene, 180g divinylbenzene, 40g methyl acrylate, 45g aromatic grafted silicon carbide nanowires prepared in Preparation Example 1, 70g toluene, 100g isobutanol, 100g normal alkane, 100g liquid wax, 100g gasoline, 5g BPO, 5g AIBN, 5g liquid bromine, and 5g nitrobenzene; the masses of the components in the aqueous phase mixture are as follows: 2000ml water, 10g cellulose, 10g calcium lignin sulfonate, 5g boric acid, 70g calcium chloride, 50g sodium chloride, 10g methylene blue, and 5g gelatin.
[0032] The preparation steps are as follows: S1: weigh the monomer preparation material by mass and mix them evenly; weigh the aqueous phase mixture by mass and mix them evenly; mix the monomer preparation material and the aqueous phase mixture evenly, first heat it to 78°C, keep it warm for 2 hours, then heat it to 89°C, keep it warm for 6.5 hours, finally heat it to 97°C, keep it warm for 3.5 hours, and cool it to 60°C to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: 300 ml of 94vt% concentrated sulfuric acid, 150 ml of ethylene dichloride and the intermediate product were mixed evenly, heated to 90°C, kept warm for 8.5 hours, and cooled to 50°C to obtain a sulfonated material; S4: The sulfonated material is washed with 70vt%, 40vt%, and 20vt% dilute sulfuric acid solutions in sequence, washed with water, and then chloroacetic acid, phosphorous acid, and liquid alkali are added for transformation stabilization. The transformation stabilization time is 30 minutes. The liquid is drained, washed with water, and filtered to obtain a sulfonated resin.
[0033] Example 2 This embodiment includes the following components by mass: 220g styrene, 200g divinylbenzene, 40g methyl acrylate, 45g aromatic grafted silicon carbide nanowires prepared in Preparation Example 1, 45g toluene, 100g isobutanol, 100g normal alkane, 100g liquid wax, 100g gasoline, 5g BPO, 5g AIBN, 5g liquid bromine, 5g nitrobenzene; the masses of the components in the aqueous phase mixture are as follows: 2000ml water, 10g cellulose, 10g calcium lignin sulfonate, 5g boric acid, 70g calcium chloride, 50g sodium chloride, 10g methylene blue, and 5g gelatin.
[0034] The preparation steps are as follows: S1: weigh the monomer preparation material by mass and mix them evenly; weigh the aqueous phase mixture by mass and mix them evenly; mix the monomer preparation material and the aqueous phase mixture evenly, first heat it to 78°C, keep it warm for 2 hours, then heat it to 89°C, keep it warm for 6.5 hours, finally heat it to 97°C, keep it warm for 3.5 hours, and cool it to 60°C to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: 200 ml of 94vt% concentrated sulfuric acid, 150 ml of ethylene dichloride and the intermediate product were mixed evenly, heated to 90°C, kept warm for 8.5 hours, and cooled to 40°C to obtain a sulfonated material; S4: The sulfonated material is washed with 70vt%, 45vt%, and 20vt% dilute sulfuric acid solutions in sequence, washed with water, and then chloroacetic acid, phosphorous acid, and liquid alkali are added for transformation stabilization. The transformation stabilization time is 30 minutes. The liquid is drained, washed with water, and filtered to obtain a sulfonated resin.
[0035] Example 3 This embodiment includes the following components by mass: 200g styrene, 190g divinylbenzene, 30g methyl acrylate, 35g aromatic grafted silicon carbide nanowires prepared in Preparation Example 1, 60g toluene, 80g isobutanol, 80g normal alkane, 150g liquid wax, 150g gasoline, 5g BPO, 5g AIBN, 5g liquid bromine, and 5g nitrobenzene; the masses of the components in the aqueous phase mixture are as follows: 2100ml water, 10g cellulose, 10g calcium lignin sulfonate, 5g boric acid, 70g calcium chloride, 50g sodium chloride, 10g methylene blue, and 5g gelatin.
[0036] The preparation steps are as follows: S1: weigh the monomer preparation material by mass and mix them evenly; weigh the aqueous phase mixture by mass and mix them evenly; mix the monomer preparation material and the aqueous phase mixture evenly, first heat it to 78°C, keep it warm for 2 hours, then heat it to 89°C, keep it warm for 6.5 hours, finally heat it to 97°C, keep it warm for 3.5 hours, and cool it to 60°C to obtain a polymer; S2: The polymer is washed with 50°C water until the water is clear, then eluted with 60°C toluene until the liquid wax and styrene residues are less than 100 ppm, then eluted with 60°C methanol until the toluene residue is less than 100 ppm, and finally washed with water until no solvent residue is left, dried and sieved to obtain an intermediate product; S3: 200 ml of 94vt% concentrated sulfuric acid, 150 ml of ethylene dichloride and the intermediate product are mixed evenly, heated to 90° C., kept warm for 8 hours, and cooled to 50° C. to obtain a sulfonated material; S4: The sulfonated material is washed with 70vt%, 45vt%, and 20vt% dilute sulfuric acid solutions in sequence, washed with water, and then chloroacetic acid, phosphorous acid, and liquid alkali are added for transformation stabilization. The transformation stabilization time is 40 minutes. The liquid is drained, washed with water, and filtered to obtain a sulfonated resin.
[0037] Example 4 The difference between this embodiment and embodiment 3 is that the following components are included: 220g styrene, 200g divinylbenzene, 30g methyl acrylate, 40g aromatic grafted silicon carbide nanowires prepared in Preparation Example 1, 60g toluene, 80g isobutanol, 80g normal alkane, 150g liquid wax, 150g gasoline, 5g BPO, 5g AIBN, 5g liquid bromine, 5g nitrobenzene; the masses of the components in the aqueous phase mixture are as follows: 2100ml water, 10g cellulose, 10g calcium lignin sulfonate, 5g boric acid, 70g calcium chloride, 50g sodium chloride, 10g methylene blue, and 5g gelatin.
[0038] Example 5 The difference between this embodiment and embodiment 3 is that the following components are included: 200 g styrene, 190 g divinylbenzene, 30 g methyl acrylate, 35 g aromatic grafted silicon carbide nanowires prepared in preparation example 3, 60 g toluene, 80 g isobutyl alcohol, 80 g normal alkane, 150 g liquid wax, 150 g gasoline, 5 g BPO, 5 g AIBN, 5 g liquid bromine, 5 g nitrobenzene; the masses of the components in the aqueous phase mixture are as follows: 2100 ml water, 10 g cellulose, 10 g calcium lignin sulfonate, 5 g boric acid, 70 g calcium chloride, 50 g sodium chloride, 10 g methylene blue, and 5 g gelatin.
[0039] Example 6 The difference between this embodiment and embodiment 3 is that the following components are included: 200g styrene, 190g divinylbenzene, 30g methyl acrylate, 35g aromatic grafted silicon carbide nanowires prepared in Preparation Example 4, 60g toluene, 80g isobutanol, 80g normal alkane, 150g liquid wax, 150g gasoline, 5g BPO, 5g AIBN, 5g liquid bromine, 5g nitrobenzene; the masses of the components in the aqueous phase mixture are as follows: 2100ml water, 10g cellulose, 10g calcium lignin sulfonate, 5g boric acid, 70g calcium chloride, 50g sodium chloride, 10g methylene blue, and 5g gelatin.
[0040] Comparative Example Comparative Example 1 The difference between this embodiment and embodiment 3 is that the following components are included: 200g styrene, 190g divinylbenzene, 30g methyl acrylate, 35g aminosilane grafted silicon carbide nanowires prepared in Preparation Example 2, 60g toluene, 80g isobutanol, 80g normal alkane, 150g liquid wax, 150g gasoline, 5g BPO, 5g AIBN, 5g liquid bromine, 5g nitrobenzene; the masses of the components in the aqueous phase mixture are as follows: 2100ml water, 10g cellulose, 10g calcium lignin sulfonate, 5g boric acid, 70g calcium chloride, 50g sodium chloride, 10g methylene blue, and 5g gelatin.
[0041] Comparative Example 2 The only difference between this embodiment and embodiment 3 is that the following components are included: 200 g styrene, 190 g divinylbenzene, 30 g methyl acrylate, 35 g silicon carbide nanowires, 60 g toluene, 80 g isobutanol, 80 g normal alkanes, 150 g liquid wax, 150 g gasoline, 5 g BPO, 5 g AIBN, 5 g liquid bromine, 5 g nitrobenzene; the masses of the components in the aqueous phase mixture are as follows: 2100 ml water, 10 g cellulose, 10 g calcium lignin sulfonate, 5 g boric acid, 70 g calcium chloride, 50 g sodium chloride, 10 g methylene blue, and 5 g gelatin.
[0042] The silicon carbide nanowires in this preparation example have a diameter of 0.1-0.5 μm and a length of 10-50 μm.
[0043] Performance test test 1: Specific surface area: The specific surface area of the adsorption resins prepared in the examples and comparative examples was tested by a fully automatic BET specific surface (area) analysis tester. The results are shown in Table 1.
[0044] Test 2: Static adsorption test: Static adsorption was used to determine the adsorption performance of the resins prepared in the examples and comparative examples for heavy metal ions. 0.1 g of the resin was placed in 50 mL of 200 mg·L -1 Heavy metal ion Cu 2 + solution in a conical flask, shake at 150 rpm, and record the adsorption amount of the resin after 8 hours. The results are shown in Table 1. The adsorption amount of the resin is calculated according to the following formula: Where qe is the equilibrium adsorption capacity, mg·g –1 ; C0 and Ce are the initial concentration and equilibrium concentration of metal ions in the solution, mg·L –1 ; m is the mass of the adsorption resin, g. The results are shown in Table 1.
[0045] Test three: Annual dissolution rate (360 cycles) test method: measure 10g of adsorption resin, dry to constant weight w1 (accurate to 0.1mg), adsorption and desorption is one cycle, after 30 cycles, take out the adsorbent, dry to constant weight w2 (accurate to 0.1mg), annual dissolution rate (360 cycles) La = (w1-w2) / w1 / 30x360x100%, the results are shown in Table 1.
[0046] Table 1 This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a sulfonated resin for heavy metal adsorption, characterized in that: The steps include: S1: Evenly mix styrene, divinylbenzene, methyl acrylate, aromatic hydrocarbon grafted silicon carbide nanowires, toluene, isobutyl alcohol, normal alkane, liquid wax, gasoline, BPO, AIBN, liquid bromine, and nitrobenzene to obtain a monomer formulation; evenly mix water, cellulose, calcium carbonate, boric acid, calcium chloride, and sodium chloride to obtain an aqueous phase mixture; evenly mix the monomer formulation and the aqueous phase mixture, raise the temperature, and keep the temperature to react to obtain a polymer; S2: washing the polymer with water, washing with an organic solvent, drying the powder and sieving it to obtain an intermediate product; S3: preparing acid solution, mixing the acid solution, ethylene dichloride and the intermediate product uniformly, heating, keeping the temperature for reaction, and cooling to obtain the sulfonated material; S4: The sulfonated material is diluted and washed with a sulfuric acid solution, washed with water, and then chloroacetic acid, phosphorous acid, and liquid alkali are added for transformation and stabilization, the liquid is drained, washed with water, and filtered to obtain a sulfonated resin.
2. The method for preparing a sulfonated resin for heavy metal adsorption according to claim 1, characterized in that: Said The mass parts of each component in the monomer formulation in S1 are as follows: 190-220 parts of styrene, 180-200 parts of divinylbenzene, 15-40 parts of methyl acrylate, 25-45 parts of aromatic grafted silicon carbide nanowires, 45-70 parts of toluene, 50-100 parts of isobutanol, 50-100 parts of normal alkanes, 100-200 parts of liquid wax, 100-200 parts of gasoline, 2-5 parts of BPO, 3-5 parts of AIBN, 5-10 parts of liquid bromine, and 5-10 parts of nitrobenzene; the mass parts of each component in the aqueous phase mixture are as follows: 2000-2200 parts of water, 5-10 parts of cellulose, 5-10 parts of calcium lignin sulfonate, 5-10 parts of boric acid, 50-70 parts of calcium chloride, 50-80 parts of sodium chloride, 2-10 parts of methylene blue, and 5-10 parts of gelatin.
3. The method for preparing a sulfonated resin for heavy metal adsorption according to claim 1, characterized in that: The mass ratio of styrene, divinylbenzene, aromatic hydrocarbon grafted silicon carbide nanowires and toluene is (5.5-6.5): (5-6): 1: 1.
5.
4. The method for preparing a sulfonated resin for heavy metal adsorption according to claim 1, characterized in that: The preparation steps of the aromatic hydrocarbon grafted silicon carbide nanowires include: adding tetra(4-carboxyphenyl)silane and silicon carbide nanowires to an ethanol aqueous solution, stirring evenly, adjusting the pH value, heating for reaction, centrifugal separation, washing, and drying to obtain the aromatic hydrocarbon grafted silicon carbide nanowires.
5. The method for preparing a sulfonated resin for heavy metal adsorption according to claim 4, characterized in that: The silicon carbide nanowire has a diameter of 0.1-1.0 μm and a length of 10-100 μm.
6. The method for preparing a sulfonated resin for heavy metal adsorption according to claim 1, characterized in that: The acid concentration in S3 is 90-94vt%, the mixing time is 25-35 minutes, the heating temperature is 80-115°C, the heat preservation time is 8-8.5 hours, and the cooling temperature is 40-50°C.
7. The method for preparing a sulfonated resin for heavy metal adsorption according to claim 1, characterized in that: The dilution and washing step in S4 includes: washing with 70vt%, 45vt, and 20vt% dilute sulfuric acid solutions in sequence, and the transition stabilization time is 30-40 minutes.
8. A sulfonated resin for heavy metal adsorption, characterized in that: The method for preparing the sulfonated resin for heavy metal adsorption according to any one of claims 1 to 7 is obtained.